2010
DOI: 10.1016/j.bbadis.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of APOBEC-1 Complementation Factor trafficking in mouse models of obesity and its positive correlation with the expression of ApoB protein in hepatocytes

Abstract: APOBEC-1 Complementation Factor (ACF) is an RNA-binding protein that interacts with apoB mRNA to support RNA editing. ACF traffics between the cytoplasm and nucleus. It is retained in the nucleus in response to elevated serum insulin levels where it supports enhanced apoB mRNA editing. In this report we tested whether ACF may have the ability to regulate nuclear export of apoB mRNA to the sites of translation in the cytoplasm. Using mouse models of obesity-induced, insulin resistance and primary hepatocyte cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 59 publications
6
15
0
Order By: Relevance
“…CRISPR-Cas9-induced deletion of A1CF led to 72% and 65% reduction in secreted APOB100 compared to control cells in Huh7 and HepG2 human hepatoma cells, respectively ( Figure 1A – 1C ; Supplementary Figure 8 ). These findings are consistent with previous studies in rat primary hepatocytes that also showed significantly decreased apoB secretion after RNAi-based depletion of A1CF 29 . Additionally, cellular APOB100 levels were significantly reduced in A1CF-deficient cells ( Supplementary Figure 8B and 8C ).…”
supporting
confidence: 93%
“…CRISPR-Cas9-induced deletion of A1CF led to 72% and 65% reduction in secreted APOB100 compared to control cells in Huh7 and HepG2 human hepatoma cells, respectively ( Figure 1A – 1C ; Supplementary Figure 8 ). These findings are consistent with previous studies in rat primary hepatocytes that also showed significantly decreased apoB secretion after RNAi-based depletion of A1CF 29 . Additionally, cellular APOB100 levels were significantly reduced in A1CF-deficient cells ( Supplementary Figure 8B and 8C ).…”
supporting
confidence: 93%
“…This report does not represent the first suggestion that A1CF may be important in nonediting-related RNA biology. In hepatic cells, A1CF has been shown to regulate both the stability (Blanc et al 2010) and the subcellular localization of specific mRNAs (Galloway et al 2010). Additional work demonstrated that A1CF behaves as a nuclear shuttling protein (Blanc et al 2003), and the shuttling is mediated by its interaction with APOBEC1 (Chester et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…These findings suggest a model whereby A1CF's primary role is to regulate the nuclear export of specific mRNA species. There is also evidence to suggest that A1CF itself is sensitive to metabolic changes (Sowden et al 2002(Sowden et al , 2004Blanc et al 2003) or disease state (Galloway et al 2010), and it remains an open question whether altered A1CF changes affect C-to-U editing in those kinds of environments.…”
Section: Discussionmentioning
confidence: 99%
“…A1 and A1CF knockout mouse models revealed that A1CF was required for embryogenesis, whereas A1 was not an essential gene, suggesting that A1CF is required for other processes. The function of A1 and A1CF can be modulated by the expression of RNA spliced variants as well as through metabolic regulation of protein post‐translational modification that determines the subcellular localization of A1 and A1CF, editosome assembly and editing activity …”
Section: Apobec1 (A1) the Rna Editing Enzymementioning
confidence: 99%
“…Tight control over AID expression and its nuclear import are among the many mechanisms whereby cells subvert AID promiscuous activity at other sites within the genome . In contrast, A1 and A1CF expression are constitutive and they shuttle from the cytoplasm to the nucleus as part of normal cell physiology . The question of how cells control A1 selection for cellular RNA over ssDNA as substrates and mitigate the oncogenic potential of A1 has never been addressed.…”
Section: Apobec1 (A1) the Rna Editing Enzymementioning
confidence: 99%